Physical Literacy: Getting Kids Active for Life. (2nd September 2016) - Stevens-Smith, Deborah A.
Abstract : The purpose of this article is to explore the context of the physical literacy movement and how it can impact play and participation. The article is intended to assist play advocates (i.e., physical education, recreation, sport educators) in implementing quality programs linked to curricular outcomes designed to foster the development of physically literate students. It is also intended to bridge a significant gap that often exists between sport, play and physical education. This article will compare physical literacy to similar concepts of literacy in language arts, math and music. Physical literacy has the potential to affect the students of today, not only so they are better prepared to lead healthy and active lives, but so they are better prepared to help others and to generate new and innovative ideas.